The Economics of Education and Training - Dustmann, Christian; Fitzenberger, Bernd; Machin, Stephen; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2008)
Education and training are key to explain the current competitive strengths of national economies, and to secure future competitiveness. While in the past educational and training institutions were often seen as providers of necessary skills for national economies, this view has changed dramatically, with education and training now being seen as a key ingredient for international competitiveness. This collection of papers on various aspects of the economics of education and training reflects this new interest. Reflecting state-of the art research in a cross country comparison, the topics covered are financing of education, transition from school to work, organisation of education, school quality and issues that relate to it, like quality of peers and teacher quality. Some papers also address issues that relate to more vocational training activities, and how these are influenced by purpose-made programmes, or other institutions.
Editorial: the economics of education and training -- Does reducing student support affect scholastic performance? Evidence from a Dutch reform -- Part-time work, school success and school leaving -- Time to learn? The organizational structure of schools and student achievement -- Who actually goes to university? -- Does the early bird catch the worm? -- Peer effects in Austrian schools -- Fair ranking of teachers -- School composition effects in Denmark: quantile regression evidence from PISA 2000 -- What accounts for international differences in student prformance? A re-examination using PISA data -- PISA: What makes the difference? -- The impact of unionization on the incidence of and sources of payment for training in Canada -- Evaluating multi-treatment programs: theory and evidence from the U.S. Job Training Partnership Act experiment -- Employment effects of the provision of specific professional skills and techniques in Germany.
Keywords: Education; Economics; Management science; Econometrics; Labor economics; Sociology; Economics; Economics, general; Labor Economics; Econometrics; Sociology, general; Education, general; Electronic books